MENINGKATKAN PRESTASI BELAJAR ILMU PENGETAHUAN SOSIAL MELALUI METODE PERMAINAN KUIS CERDAS CERMAT - Sidiq Sidiq (HUMANIS: Jurnal Ilmu-Ilmu Sosial dan Humaniora, 2018)
This study aims to determine the implementation of learning using quiz intelligent quiz methods and the improvement of social science learning achievement of the sixth grade students of SD Negeri Wudi, Sambeng Sub-district, Lamongan Regency in the academic year 2016/2017. The subject of this research is the entire class VI SD Negeri Wudi which amounts to 9 people. This study belongs to a classroom action research consisting of several cycles with each cycle consisting of planning, action, observation, and reflection. Instruments used in the form of Learning Plans (RP), Student Activity Sheets (LKS), and grade assessment. The results showed an increase in student learning outcomes. In the first cycle there are 4 students who experience complete learning of individuals from 9 the number of students (44.44%), in this cycle has not occurred classical mastery. In the second cycle there are 8 students who experience complete learning of individuals from 9 the number of students (88.89%), in this cycle has occurred classical mastery.